Implementasi Quick Response (QR) Code Pada Dokumen Instruksi Kerja Alat Laboratorium Kimia - W Wangsa; P Prastyo (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
Work instructions laboratory equipment is one of the documents that must be available in the laboratory. This document provides information on the operation steps of the device correctly. A laboratory manager usually prints the document on A4 size paper and installs it on a part of the tool to facilitate access to the document. The treatment makes the work instruction document break down quickly and is not suitable to be applied to small sized tools. Therefore, it is necessary to manage the work instruction document for easy access, efficiency in the use of documents, and to improve the security of document storage. In this case, the QR Code can be used as a solution to the problem. QR Code is able to store documents and URL links in a small barcode image so that it can be use more efficient. Making a QR Code is preceded by storing documents at https://drive.google.com. The URL link at https://drive.google.com is entered into the QR-Code Studio 1.0 application and converted into a barcode. Barcodes are then printed and installed on each laboratory instrument. Scanning QR Code using a smartphone application in the form of a QR-Code Scanner. The results of the barcode scanned are the form of scripts for laboratory work instructions